2016
DOI: 10.1182/bloodadvances.2016001651
|View full text |Cite
|
Sign up to set email alerts
|

Accurate, simple, and inexpensive assays to diagnose F8 gene inversion mutations in hemophilia A patients and carriers

Abstract: Key Points• Improved assays to detect intron 22 and intron 1 inversions in the F8 gene have been developed.• These assays can efficiently detect or rule out the most common genetic mutations resulting in hemophilia A.The most frequent mutations resulting in hemophilia A are an intron 22 or intron 1 gene inversion, which together cause ;50% of severe hemophilia A cases. We report a simple and accurate RNA-based assay to detect these mutations in patients and heterozygous carriers.The assays do not require speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…FVIII protein, which is secreted by the vascular ECs, 61,62 is an essential coagulation cofactor that amplifies thrombin generation, and hence blood clotting by accelerating the enzymatic activity of the serine protease factor IXa. 29,63 We found that DRAGA lung epithelium was reconstituted with 10-12% of human CD36 + ECs. Furthermore, severe H1N1/PR8 infection of DRAGA mice resulted in undetectable human and murine F8 mRNA expression in the damaged lung areas.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…FVIII protein, which is secreted by the vascular ECs, 61,62 is an essential coagulation cofactor that amplifies thrombin generation, and hence blood clotting by accelerating the enzymatic activity of the serine protease factor IXa. 29,63 We found that DRAGA lung epithelium was reconstituted with 10-12% of human CD36 + ECs. Furthermore, severe H1N1/PR8 infection of DRAGA mice resulted in undetectable human and murine F8 mRNA expression in the damaged lung areas.…”
Section: Discussionmentioning
confidence: 93%
“…The so-called "cytokine storm" referring to the release of inflammatory cytokines by infiltrating lymphocytes in infected lungs can be a significant damaging event. 29 Severely infected F1, M4, and M5 mice showed slightly, but not significantly higher IFNγ RNA expression in affected areas of the lungs than non-infected mice (*p = .03), whereas the TNFα RNA expression was significantly higher in the infected mice (*p = .004) ( Figure 2). No differences in human IFNγ and TNFα RNA expression were detected by RT-qPCR between the non-affected lung area from infected and non-infected mice (data not shown), and no human IFNγ and TNFα RNA was present in non-HIS humanized DRAGA mice ( Figure 2).…”
Section: Draga Mice Sustain Sub-lethal Infection With A/h1n1/ Pr8 Virusmentioning
confidence: 93%
See 1 more Smart Citation
“…Inversion disruption of the F8 gene is not only the most common variant found in patients with severe HA, [30][31][32][33][34][35][36] but it is also the most common found in canine HA models. 37 Approximately one-half of cases of severe HA are caused by an inversion variant of the F8 gene, with a frequency of 40% to 50% in intron 22 and 1% to 5% in intron 1.…”
Section: Discussionmentioning
confidence: 99%
“…Inv1 inversions are present in 1%–2% of HA patients 1 . Inv1 genotyping has been performed using long‐range polymerase chain reaction (PCR), 2 inverse‐shifting PCR, 3 and an RNA‐based method 4 …”
Section: Introductionmentioning
confidence: 99%